The Public Appreciation Towards Campaign Media Of Regional Election In West Java, Indonesia - Octavianti, Meria; Ira Mirawati, Ira Mirawati (2015)
Various studies show that the media plays an important role in political contexts including in the regional head election. Previous study shows that the campaign media management gives a significant contribution to influence perception, attitude, and behavior of voters. So, campaign media management is one of the important factors needed to be considered by the candidates and managed professionally so it can provide a significant impact to influence voters. The purpose of this study is to describe and analyze the responses or public appreciation towards the campaign media of regional head election in West Java, Indonesia.